2021
DOI: 10.3389/fonc.2021.641955
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Death Risk in Primary Central Nervous System Lymphoma Patients Treated With Chemotherapy: A Registry-Based Cohort Study

Abstract: PurposeTo study the cardiovascular death (CVD) risk in primary central nervous system lymphoma (PCNSL) patients with chemotherapy.MethodsWe obtained 2,020 PCNSL participants and 88,613 non-central nervous system lymphoma (NCNSL) participants with chemotherapy from Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2015. A 1:3 propensity score matching (PSM) was used to reduce the imbalance between PCNSL participants with and without chemotherapy, as well as the imbalance between PCNSL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…This result seemed to be contrary to the observed cardiotoxic effect of chemotherapy. However, consistent with the previous studies in other tumors ( 29 , 30 ), this contradiction arises from the limited life expectancy of patients who received chemotherapy and succumbed to CVD events. Since the detailed information for chemotherapy regimen were missing in the SEER database, further investigation is required to clarify the effect of chemotherapy on the risk of CVD among patients with CRC.…”
Section: Discussionsupporting
confidence: 84%
“…This result seemed to be contrary to the observed cardiotoxic effect of chemotherapy. However, consistent with the previous studies in other tumors ( 29 , 30 ), this contradiction arises from the limited life expectancy of patients who received chemotherapy and succumbed to CVD events. Since the detailed information for chemotherapy regimen were missing in the SEER database, further investigation is required to clarify the effect of chemotherapy on the risk of CVD among patients with CRC.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, first-line treatment with HD-MTX and autologous stem cell transplantation has been shown to be feasible and effective since 2011 (2). Supporting evidence has also been derived from a multi-center retrospective study (9), which concluded that the risks of CVD-associated deaths were 50% lower in PCNSL patients diagnosed in 2010-2015 than in those diagnosed in [2004][2005][2006][2007][2008][2009].…”
Section: Discussionmentioning
confidence: 99%
“…Participant variables included sex (male/female), race (White/Black/others), age at diagnosis (< 60 years/≥ 60 years) ( 15 ), year of diagnosis (2007–2011/2012–2016), marital status (married/unmarried), pathological type (DLBCL/others), surgery (yes/no evidence), radiotherapy (yes/no evidence), and chemotherapy (yes/no evidence) ( 9 ). Other races included American Indian/Alaska Native and Asian/Pacific Islander.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the SEER database, Guan et al. found that chemotherapy was associated with a lower cardiovascular death risk in primary central nervous system lymphoma patients than those without chemotherapy ( 16 ). Janick Weberpals found that a long-term heart-specific mortality among breast cancer survivors treated with chemotherapy or radiotherapy is not increased compared with the general population ( 17 ).…”
Section: Introductionmentioning
confidence: 99%